2017
DOI: 10.1002/ccr3.1297
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected discovery of multiple myeloma following cardiomyopathy

Abstract: Key Clinical MessageWe report the case of multiple myeloma of unexpected discovery in an old patient admitted to the emergency department of cardiomyopathy. This observation emphasizes the need for exploring any anemia before linking it to heart failure or kidney disease. Serum protein electrophoresis remains crucial especially in the elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Myocardial involvement is estimated to be present in half of the amyloid light chain amyloidosis cases, which may subsequently result into restrictive physiology and CM [30,34]. These findings support the observation made in several case reports of the relationship between MM and amyloidosis in the development of CM [29,30]. MM has also been associated with a specific set of clinical manifestations often referred to as CRAB (elevated Calcium levels, Renal insufficiency, Anaemia and Bone lesions), which may increase the risk of CV comorbidities [35].…”
Section: Haematologic Cardiomyopathysupporting
confidence: 70%
See 2 more Smart Citations
“…Myocardial involvement is estimated to be present in half of the amyloid light chain amyloidosis cases, which may subsequently result into restrictive physiology and CM [30,34]. These findings support the observation made in several case reports of the relationship between MM and amyloidosis in the development of CM [29,30]. MM has also been associated with a specific set of clinical manifestations often referred to as CRAB (elevated Calcium levels, Renal insufficiency, Anaemia and Bone lesions), which may increase the risk of CV comorbidities [35].…”
Section: Haematologic Cardiomyopathysupporting
confidence: 70%
“…It is the second most prevalent haematological malignant abnormality with an annual age-adjusted incidence of 6.3 per 100,000 persons in the U.S. [24] and accounts for approximately 10% of all haematological cancers [26][27][28]. Anaemia is a common complication observed in about two-thirds of MM patients [29]. A triad of chronic kidney disease, HF and anaemia has been described in clinical practice [29,30].…”
Section: Haematologic Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have analyzed the pathogenesis of ACM, which includes cardiac toxicity induced by the principal metabolites of ethanol ( 17 , 18 ), apoptosis ( 19 ), mitochondrial dysfunction ( 20 ) and abnormal energy metabolism of cardiomyocytes, nutrient imbalance, ventricular remodeling ( 21 , 22 ), disorders of the neurohumoral system ( 23 , 24 ), abnormal cell signal transduction and immunological and inflammatory reactions ( 25 ). Studies have reported that ethanol-induced apoptosis serves a key role in the pathogenesis of ACM ( 26 29 ). A study on the mechanism of ethanol-induced cardiomyocyte apoptosis demonstrated that the levels of tumor necrosis factor-α, the apoptotic protein Bcl-2-associated X and caspase-3 are significantly increased in ACM ( 30 ).…”
Section: Discussionmentioning
confidence: 99%